Three facets of urban metabolism (case of Kazakhstan) - Aizhan T. Tleuberdinova; Nailya K. Nurlanova; Farida G. Alzhanova; Bekmukhamed T. Kalmenov (International Journal of Urban Sustainable Development)
The urbanisation growth causes problems related to the provision and consumption of resources, ecology, and social living conditions in cities. The purpose of the article is to study the dependence of metabolic factors and the level of urban conveniences on the urbanisation level and to justify the need to monitor these processes and improve the management of urban systems with the purpose to achieve sustainable development objectives. Three aspects of the problem of urban metabolism and sustainable development of cities are considered in the article. They are energy consumption by megacities, social aspects of metabolism and growth of megacities, problems of urban improvement. The increasing risks of negative impact of urban growth on the environment and living conditions has been proven. It is shown that the resettlement flow of village residents to cities, especially large ones, remains high despite the deterioration of the environmental situation in large cities and the lag in the urban infrastructure development from the population growth rate. The expediency to expand the context of the urban metabolism problem was noted, including the exchange of resources between urban and rural to reduce spatial inequality, and to increase the sustainability of urban and rural settlements.